2021
DOI: 10.1016/j.braindev.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Tremor as an early sign of hereditary spastic paraplegia due to mutations in ALDH18A1

Abstract: Background: The ALDH18A1 gene is located at 10q24.1 and encodes delta-1-pyrroline-5-carboxylate synthetase (P5CS), a mitochondrial bifunctional enzyme that catalyzes the first two steps in de novo biosynthesis of proline, ornithine, citrulline, and arginine. ALDH18A1-related disorders have been classified into four groups, such as autosomal dominant and recessive hereditary spastic paraplegia (SPG9A and SPG9B, respectively), as well as autosomal dominant and recessive cutis laxa (ADCL3 and ARCL3A, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…At age 36, the patient manifested, in addition to severe spasticity of the legs, distal amyotrophy, and pes cavus, sensory neuropathy, spasticity of the bulbar region, as well as mild cerebellar signs with nystagmus and past-pointing in the arms. This is the first report of SPG9B in sub-Saharan Africa, with previous reports in European and Japanese populations ( 53 , 54 ). The majority of these missense variants occur in the L-glutamyl-5-phosphate reductase (G5PR) domain, where the p.Val451Met variant is also located.…”
Section: Resultssupporting
confidence: 69%
“…At age 36, the patient manifested, in addition to severe spasticity of the legs, distal amyotrophy, and pes cavus, sensory neuropathy, spasticity of the bulbar region, as well as mild cerebellar signs with nystagmus and past-pointing in the arms. This is the first report of SPG9B in sub-Saharan Africa, with previous reports in European and Japanese populations ( 53 , 54 ). The majority of these missense variants occur in the L-glutamyl-5-phosphate reductase (G5PR) domain, where the p.Val451Met variant is also located.…”
Section: Resultssupporting
confidence: 69%
“…P5CS has an important function for the regulation of glutamine metabolism and the Krebs cycle. The most important roles it plays are catalyzing the reduction conversion and coupled phosphorylation and synthesizing proline from glutamate (Guo et al, 2020;Kalmar et al, 2021;Pickwick et al, 2022). Furthermore, a recent study conducting a functional assessment of homozygous P5CS variants revealed alterations in amino acid and antioxidant metabolism (Colonna et al, 2023), which further supported the important role of P5CS in regulating the antioxidant system.…”
Section: Discussionmentioning
confidence: 81%
“…A spectrum of 13 mutations in the ALDH18A1 gene have been identified in 17 patients with autosomal recessive HSP, including 10 missenses, 2 splicing mutations, and a non-sense mutation (Table 1). Most notably, the previously reported p.R128H mutation was found in seven patients (2,3,25), making it the most frequently occurring ALDH18A1 mutation thus far identified in SPG9B patients. The patients reported to carry the p.R128H mutation invariably exhibited an earlier age of onset.…”
Section: Discussionmentioning
confidence: 87%